THE TOPIC OF WOMAN-NATURE THROUGH TWO POEMS OF SIMPLE CANCIÓN BY JUAN GONZALO ROSE - Avalos Guerra, Luis (2019)
In this article we will approach the poems "Marisel" and "Geografía implacable" by Simple canción (1960), by Juan Gonzalo Rose (1928-1983). We’ll influence women’s figures in line with the elements that constitute nature. In parallel, we’ll perform an analysis of the rhythmic dimension of both poems. Thus, and from the General Textual Rhetoric of Stefano Arduini and Oldrich Belic's theory of cognitive rhythmic semantics, we’ll say that there is a discursive construction that presents the female figure with valences from the figurative fields of metaphor and synecdoche, all enhanced from work with the rhythmic dimension of the poems. The effect that occurs on the lyrical subject decant sits on the constant anguish of the same, because it’s significantly recognized against the overflowing figure of woman.